2011
DOI: 10.1902/jop.2010.100378
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antimicrobial Susceptibility of Enterococcus Faecalis Isolated From Chronic Periodontitis in Biofilm Versus Planktonic Phase

Abstract: The E. faecalis strains of chronic periodontitis exhibited weak biofilm formation ability at the early stage. Over 50% of the strains were resistant to tetracycline, and a few strains were highly resistant to erythromycin or gentamicin. E. faecalis cells in biofilm were hardly eradicated by most of the agents, even in high concentrations. Triclosan was effective in inhibiting E. faecalis growth in both biofilm and planktonic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
7
14
0
Order By: Relevance
“…Our previous study of oral Enterococcus faecalis isolated from Norwegian patients with marginal and apical periodontitis showed that approximately 50% of the strains were resistant to one or more of the tested antimicrobial agents, mostly tetracycline and/or erythromycin [5], [6]. These observations are consistent with former studies showing resistance towards commonly used antimicrobials in enterococci isolated from the oral cavity [7], [8], [9].…”
Section: Introductionsupporting
confidence: 88%
“…Our previous study of oral Enterococcus faecalis isolated from Norwegian patients with marginal and apical periodontitis showed that approximately 50% of the strains were resistant to one or more of the tested antimicrobial agents, mostly tetracycline and/or erythromycin [5], [6]. These observations are consistent with former studies showing resistance towards commonly used antimicrobials in enterococci isolated from the oral cavity [7], [8], [9].…”
Section: Introductionsupporting
confidence: 88%
“…11,20,23 However, it has been shown that biofilms formed in the first few days of incubation may not display the same antimicrobial resistance of a mature biofilm. 24,25 According to Guerreiro-Tanomaru et al, 20 the percentage of biofilm surface coverage on bovine dentine blocks was higher at 14 days than at 21 days, with no statistical differences between the two periods, thus justifying the 14 day-incubation period used in the present research.…”
Section: Discussionsupporting
confidence: 49%
“…Enterococci are believed to be important biofilm participants (3134). Even if enterococci are not present in high numbers in the dental plaque biofilm, they may have an important role as a reservoir for antibiotic-resistant genes, which can be transferred to other bacteria in the biofilm (12, 35). …”
Section: Discussionmentioning
confidence: 99%